Papan Pintar Acak Kata for Improves Reading Skills of Grade II Elementary School Students - Ni Kadek Sintayani; I Made Citra Wibawa; Putu Aditya Antara (Universitas Pendidikan Ganesha, 2023)
The ability to read is an ability that must be possessed by students as the main capital in improving their quality. This study aims to produce learning media